Internationalization and integration via benchmarking visits: the IIUM experiences - Abdul Ghadas, Zuhairah Ariff; Mohamad, Nor Asiah (2007)
Internationalization and integration mark as one of the important visions of IIUM. In view of this, the university has established a Rectory (office of the Seputy Rector Internationalization and Innovation) as well as an International Students Office. Other than these two agencies, the Students Affairs Division, in particular, the residential accomodation (Mahallat) also plays important role to ensure that the agenda of integration and internationalization is successful in IIUM. Various efforts have been taken including several benchmarking visits to international universities. The aims of the visits is to expose the administrators of Mahallat to various aspects of the international students' life as well as the quality of services provided to the students at other universities especially in the Middle East and Asia Pacific countries. This paper highlights two benchmarking visits held in 2006 in which some of the Principals of the Mahallat were involved. The focus areas are on the students' facilities, handling of the international students' needs and cultures, security as well as fostering networking among the universities, international and locals.